(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Sonchus oleraceus L. (Asteraceae) has a widespread world distribution and is also common in Brazil. It is a dietary and traditional medicinal plant in Chinese folk culture that can be cooked and eaten to treat inflammatory disease. The aim of the present study was to offer a novel perspective on the medicinal product originating from this species and to test its hepatoprotective activity. Petroleum ether, Ethyl actate and Methanol successive extracts obtained from the aerial parts were used for hepatoprotective study. Compounds that are evaluated for this activity were Flavonoids and Sesquiterpene glycosides, that are identified and quantified by Column chromatography and H1- NMR & Mass Spectra, respectively. Hepatoprotective activity was assessed in vitro, using various biochemical parameters i.e., SGPT, SGOT, SALP, bilirubin (total & direct) and isolated liver. Hepatoprotective activity was tested in rats with experimentally-induced hepatotoxicity by CCl4. The tested extract proved significant hepatoprotective capacity under in-vitro condition. Results of the in-vivo experiment showed that prominent hepatoprotective activity was shown by successive ethyl acetate and petroleum ether extracts. In this way, the present study offered a novel perspective on the medicinal uses of the species, proving significant amounts of Flavonoids and Sesquiterpene glycosides in the composition of the aerial parts, that has proved hepatoprotective activity.